Development of a checklist for use with "clinical observations of gross motor items" tool to refine observations of dysfunction - Jordaan, Louisa Maria (My University, 2017)
Introduction Appropriate motor coordination is a prerequisite for most occupational tasks (Summers, et al., 2008) (Case-Smith & O'Brian, 2010). Young children develop motor coordination over a period of years (Case-Smith & O'Brian, 2010) (Gallahue, et al., 2012). This can be observed in the development of gross motor skills such as jumping, hopping, skipping etc. (Case-Smith & O'Brian, 2010). Delays in the development of motor coordination can thus have an effect on a child’s development in all other aspects of their life (Gallahue, et al., 2012). Problem There is a need in South Africa for a cost-effective standardised tool to evaluate motor coordination in children in a valid and reliable way. Currently standardised tools must be imported from the United States of America (USA) or the United Kingdom (UK) and may not be suitable for South African children. An evaluation tool for motor coordination does exist in South Africa, but its current scoring depends in part on the experience and skill set of the professional to judge the quality of movement during a movement task and its psychometric properties have not been explored. Aim This study aimed to identify salient behavioural characteristics that separate children with typical motor coordination development and mild to severe motor coordination dysfunction from each other on the items of the Clinical Observations of Gross Motor Items (COGMI) (SAISI, 2004), in order to provide recommendations to improve the reliability and standardization of the scoring of this tool in the 5 year 0 months – 5 years 11 months age group. Method A quantitative, comparative, descriptive, cross-sectional study design was used, with a total of 23 children in this age group. The participants were divided into a typical motor coordination (green) group and a mild to severe motor coordination dysfunction (red) group. They were videoed while performing 15 of the 18 items of the COGMI. These video recordings were analysed using movement analysis to determine specific behaviours which identify function and dysfunction in this age group. Results From the observations which could be seen when using the COGMI, clusters could be identified. As the COGMI focuses on coordination of movement rather than postures, the starting and finishing position were discarded and further analysis was only done on the movement component of items. The observations made during the movement portion of items on the COGMI were divided into observations made of the upper limbs, the lower limbs, head, neck and core. Comparisons were made between the two groups and looked at the salient behavioural characteristics that determine function and dysfunction in the age group of five year old children. Conclusion Throughout this study it was very clear that this specific age group presents with a lot of variability due to the fact that they are still developing in their gross motor skills and are not yet proficient in fundamental skills. Using these characteristics a checklist of behaviours was developed, which can be used in combination with the COGMI scoring sheet.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Occupational Therapy. Johannesburg, 2017.
Keywords: Child Development Motor Coordination